The burden of atrial fibrillation/atrial flutter in Europe from 1990 to 2021, with a forecast of incidence through 2044 - Min Xie; Xia Zhao; Bin He; Chunyan Lian; Jin Zhao; Xiaobo Li; Qi Lin (Frontiers in Cardiovascular Medicine)
BackgroundThe objective of this analysis was to assess the impact of atrial fibrillation (AF)/atrial flutter (AFL) across various European regions and countries from 1990 to 2021.MethodsUsing the global burden disease 2021 analytical tools, this study evaluated the incidence, prevalence, disability-adjusted life years (DALYs) and death associated with AF/AFL across the European Region, as defined by the World Health Organization, which includes 53 member countries (EU-53), as well as the European Union, as defined in 2019, consisting of 28 member countries (EU-28) from 1990 to 2021.ResultsThe EU-53, in 2021, there were 957,812 incident cases [95% uncertainty interval (UI): 773,898 to 1,178,186], 103,043 deaths (95% UI: 86,887 to 111,924), and 2,196,895 DALYs (95% UI: 1,847,967 to 2 596 530) attributed to AF/AFL. The age-standardized rates (ASRs) of incidence, prevalence, death, and DALYs were respectively 1.16, 1.14, 1.06, and 1.10 times higher in the EU-28 compared to the EU-53. The absolute number of AF/AFL incidents is projected to increase from 2021 to 2044 across Western Europe (from 600,735 to 723,218), Eastern Europe (from 176,794 to 190,803), and Central Europe (from 122,625 to 135,877).ConclusionDespite substantial efforts to manage AF/AFL in Europe, it remains a significant public health challenge. The burden of AF/AFL varies considerably across European countries and subregions, as well as between different EU classifications (EU-28 vs. EU-53). In Western Europe and the EU-28, which include many developed nations, higher ASRs of deaths, DALYs, prevalence, and incidence have been reported.